Model Base pada Sistem Penunjang Keputusan yang Berbasis Logika Fuzzy - Yohanes Suhari (Universitas Stikubank, 2002)
Decision support systems based on fuzzy logic may be used to solve problems to find optimum solution on fuzziness environmental. The differences with old decision support system is we can find optimum solution that more realities, because in fuzzy logic not use absolute truthful right or false. Goal of this article is how to construct model base on decision support system based on fuzzy logic.